Parasitic Infestation in Pediatric and Adolescent Appendicitis: A Local Experience - Zakaria, Ossama M. (OMJ, 2013)
OBJECTIVE: The relationship between parasites and pediatric appendicitis is a highly debatable issue. This study aims to investigate the role of parasitic infestation in the etiology of acute pediatric appendicitis. METHODS: A retrospective study including 1600 pediatric and adolescent patients who had undergone surgical therapy for a diagnosis of acute appendicitis over a period of ten years from Jan 2001 to Dec 2010. Demographic data were retrieved including the patient's age, sex, clinical data, clinical presentations, laboratory investigations, operative data and pathological findings to identify the presence and type of parasites. Patients were divided into two groups according to the presence or absence of parasites in the appendix lumen. In group I (n: 88), parasitic infestation was observed, whereas in group II (n: 1502), no parasitic infestation was present. RESULTS: Parasites were present in 5.5% (88 patients), and of those 88 parasitic infestations, 45 (51.1%) were Enterobaisis, 8 (9.1%) were Schistosomiasis, 23 (26.1%) were Ascariasis, 7 (8%) Trichuriasis, and 5 (5.7%) were Teania Saginata. The percentage of patients with suppurative, gangrenous or perforated appendicitis was similar in both groups with no statistical significance, irrespective of the presence or absence of parasitic infestation. CONCLUSION: The low prevalence of parasites among the appendectomy specimens did not support the notion that parasites were a major cause of appendicitis in pediatric patients.